(untitled) (Perspectivas em Ciência da Informação, 2009)
This paper attempts to explain technical decisions encountered on conservation and in the reformatting of analog audio materials to digital formats by examining how the curators, specialists, institutions, manuals and international guidelines deal with sound supports. The purpose is to provide and overview and begin the construction of a national conception of a more objective and satisfactory methodology, by means of the union of knowledge of the involved segments with sound supports.